Kurikulum deep learning berbasis green economy di Indonesia - Mustofa Kamil; Uyu Wahyudin; Purnomo Purnomo; Deti Nudiati; Eko Sulistiono; Mohamad Hadi Ali Mutamam; Diemas Arya Komara (Universitas Pendidikan Indonesia, 2026)
This study discusses the development and application of a green-economy-oriented deep learning curriculum, namely Literasi Ekonomi Hijau (Economy Green Literacy), in a Pusat Kegiatan Belajar Masyarakat (PKBM) in Indonesia. The program is designed to integrate Deep Learning with Environmental Sustainability Education to address local environmental issues, including waste management, water conservation, and the adoption of clean energy. Using a participatory, co-creational method, the course features hands-on projects in which learners work on environmentally sustainable initiatives such as upcycling household waste and organic farming. Findings emphasise the transformative effects on participants, including improved environmental understanding, practical skills, and community connectedness. The curriculum design encourages student–led learning and participation in local environmental solutions. This work examines the potential of merging innovative educational approaches and bottom-up sustainability initiatives to promote green economy thinking and the social innovation that follows. The study highlights the role of contextually relevant, interdisciplinary education in equipping the next generation to address environmental issues in a complex, interconnected world.